Peningkatan Ekonomi Budidaya Tanaman Hidroponik Milik Gampong Beurawe, Banda Aceh - Zulfah; Muslich Hidayat (Jurnal Riset dan Pengabdian Masyarakat, 2022)
Hydroponics is a method without using soil media, but by using a solution of minerals, sand, broken bricks, sawdust, etc. which serve as a substitute for soil media. Cultivation of hydroponic vegetables belonging to the village-owned enterprise (BUMG) of the Beurawe village was established with the aim of increasing the economic growth of the community, being able to accommodate labor, having additional income for the community.